STRATEGI BERTUTUR DALAM TINDAK TUTUR EKSPRESIF BAHASA INDONESIA PADA KEGIATAN DISKUSI - Nurhamida, Nurhamida; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
AbstractÂ The purpose of this research is describe the shape, strategy and function in activities of the discussion in class VII SMP Negeri 13 Padang. This type of research is a qualitative method descriptive. Data in this study is the shape and strategy of said expresive of students is a discussion activity. The data source in this study was the student in the discussion activities in class VII SMP Negeri 13 Padang. The data collection techniques in this study are recording techniques, observations, and record-taking techniques. Based on the findings of research, we can conclude things here. There are six of the said thisplays used students in the discussion, which is say thank you 29 utterance, to say i am sorry 7 utterance, praising 3 utterance, criticizing 12 utterance, angry 11 utterance and complaining 4 utterance. Â The six of the said expressive was told by using four strategies are recalled, namely frankly without further ado 48 utterance, frankly speaking with positive civility 3 utterance, to be bright with negative civility 5 utterance, and said vaguely 10 utterance.Â Kata kunci: tindak tutur, ekspresif, strategi, diskusi